A New Framework to Explore High‐End Sea Level Rise for the UK: Updating H - Weeks, J. H.; Allison, L. C.; Beverton, A.; Lowe, J. A.; Orr, H. G.; Roberts, H.; Palmer, M. D. (Earth's future, 2025)
The UK high‐plus‐plus (H++) scenario for high‐end sea level rise is used in sensitivity testing for significant infrastructure (e.g., nuclear facilities) and forms part of the Environment Agency planning guidance in England. However, the existing H++ scenario, developed as part of the UK Climate Projections in 2009 (UKCP09), does not reflect the latest science knowledge on ice sheet instability processes and has limitations, as revealed in consultations with users of this information. Here, we outline a new, co‐produced H++ framework to inform decision‐making that involves: (a) screening decisions against an updated H++ storyline that reflects major scientific advances since UKCP09; (b) evaluating adaptation options and damage costs against a wider library of alternative, plausible storylines; and, (c) a decision‐exploring initiative to facilitate long‐term strategic thinking. Our H++ screening storyline is based on the Intergovernmental Panel on Climate Change Sixth Assessment Report low‐likelihood high‐impact sea level rise assessment. In response to user needs, all storylines within the H++ framework provide time‐continuous, geographically‐specific sea level rise projections for the UK to 2300 and information on sea level rise rates. For all UK capital city locations, our screening storyline projects high‐end sea level rise greater than: 1 m by 2100; 4 m by 2150; 9 m by 2200; and, 15 m by 2300. At all locations, maximum rates reach over 100 mm/yr. Our H++ framework can be adapted for different climate impact drivers, sectors or regions, and respond to emerging evidence and user feedback, supporting robust adaptation planning and decision‐making under deep uncertainty. Plain Language Summary Globally, sea levels are rising because of climate change. Climate models indicate sea levels will continue rising for centuries. There is potential for several meters or more of sea level rise outside the expected range if “runaway” ice sheet processes are triggered. Despite incomplete scientific understanding of these processes, coastal planners managing the Thames Barrier, decision‐makers operating nuclear power facilities, and others, need to prepare for the possibility of “high‐end” sea level rise. We propose an update to the existing high‐end sea level rise scenario for the UK (the “H++ scenario”) published in 2009. Our update involves steps to explore how high‐end sea level rise could affect decision‐making: (a) screening decisions using an updated high‐end sea level rise projection that is plausible, but not necessarily probable, and describes the amount of rise and the processes driving it; (b) consideration of adaptation options and damage costs against a wider library of alternative sea level rise possibilities; and, (c) strategies (e.g., decision‐gaming) to explore and verbalize the decision‐making process under different futures. Sea level projections are available to 2300 for coastal locations around the UK, including information on rates. Our flexible approach could be adapted for different climate hazards, sectors or regions. Key Points We present a pragmatic and flexible framework to inform robust exploration of high‐end sea level rise (H++) in coastal resilience planning Our framework features a screening process, a database of plausible projections, and a decision‐exploring initiative Our dynamic framework can accommodate user feedback and emerging scientific knowledge on ice sheet instability mechanisms